Clinical researchPrevalence of cellulitis and erysipelas in post-mastectomy patients after breast cancer - de Godoy, José Maria Pereira; da Silva, Silvia H. (Archives of Medical Science, 2007)
Introduction: Cellulitis and erysipelas are common complications of lymphedema but have been reported in few cases following treatment for breast cancer. These are superficial skin infections which are spread by lymphatic vessels and can result in permanent injury of vessels. The possibility of these infections triggering or aggravating lymphedema may result in greater discomfort for patients in the post-operative period of breast cancer. The object of the current report was to evaluate the prevalence of cellulitis and erysipelas in post-mastectomy patients. Material and methods: Ninety women from the region of Catanduva, Sa~o Paulo, who submitted to a mastectomy for breast cancer were evaluated and selected using the patients’ records from a Government Health Clinic and the School of Physiotherapy in Catanduva-IMES. The patients were assessed with respect to the occurrence of events of erysipelas which were confirmed and treated by a physician. As a control, the contralateral limbs were investigated. The Fisher exact test was used for statistical analysis and an alpha error of 5% was considered acceptable. Results: Episodes of erysipelas and cellulitis of the ipsilateral limb were reported by 25.5% of the women whereas no cases of the involvement of contralateral limbs were described giving a statistically significant difference. Conclusions: There is a significant association between cellulitis and erysipelas with the surgical treatment of breast cancer.